CURRENT APPROACHES TO CHEMORADIOTHERAPY FOR MALIGNANT GLIOMAS - Ye. L. Choinzonov; O. V. Gribova; Zh. A. Startseva; A. I. Ryabova; V. A. Novikov; L. I. Musabayeva; I. S. Polezhayeva (Бюллетень сибирской медицины)
High-grade malignant gliomas (WHO grade G III–IV) account for more than 50% of all primary brain tumors. Despite aggressive treatment, survival rates are still very low with a median reported survival of no more than 1.5 years.Radiation therapy is an integral part of the combined treatment, but often does not influence lethally on resistant tumor cells. Thereby, in recent decades there has been an active search for novel approaches to the treatment of malignant gliomas (chemotherapeutic drugs, biological modifiers, local hyperthermia). Experimental data showed that the effect of high temperatures has both a direct damaging effect on tumor cells and a sensitizing effect. Significant advantages are achieved when the complex treatment of different malignant tumorsincludes local hyperthermia. However data on the treatment of patients with primary and recurrent gliomas G III–IV using local hyperthermia are scarce.The literature review is given in the article provides an overview of the existing treatment methods for brain tumors.